COVID-19 rapid evidence profile #9: What is the incremental benefit of using a history of sudden loss of taste (ageusia) and/or smell (anosmia) in symptom screening to identify people who may have COVID-19 and need to take appropriate action? - Waddell, K; Wilson, MG; Gauvin, François-Pierre; Mansilla, C; Moat, KA; Wang, Q; Lavis, JN (My University, 2020)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about incremental benefit of using a history of sudden loss of taste (ageusia) and/or smell (anosmia) in symptom screening to identify people who may have COVID-19 and need to take appropriate action in response to a decision-maker’s request.
Keywords: incremental; benefit; history; ageusia; anosmia; screening; COVID-19